Multi-Proxy reconstruction of South Asian Monsoon variability in Sri Lanka - Henadheera Arachchige, Kasun Gayantha (2021)
The South Asian Monsoon (SAM) brings precipitation crucial for agriculture and public health across the densely-populated region of Southeast Asia. Identifying the key long-term drivers of the SAM is essential to improve the predictability of future monsoonal trends in the context of current global climate scenarios and increasing drought and flooding events in this part of the world. Here, we reconstruct ~6000 years of climate and environmental history of South Asian summer monsoon-fed Bolgoda South Lake and the Horton Plains, and the winter monsoon-fed Panama lagoon in Sri Lanka to understand better the operation of the Indian Ocean summer and winter monsoons over this island and their connection to broader climate systems. Multi-proxy trends (diagnostic biomarkers, hydrogen and carbon isotopes of individual n-alkane, grain size, and XRF elemental ratios) indicated a sub-millennial scale decreasing trend of summer monsoon rainfall in the wet zone of Sri Lanka alongside an increasing trend of the winter monsoon in the dry zone. We also observed multi-centennial scale arid events in the Bolgoda South Lake and Horton Plains records at ~3,500 and ~250 cal years BP. The observed inverse monsoonal behaviour during the mid- and late Holocene seems to be led by the southward migration of the mean latitudinal position of ITCZ, induced by varying solar energy distribution between Northern and Southern hemisphere due to Earths processional cycle. Our observations are broadly supported by existing palaeoclimatic records from the Indian sub-continent, despite timing of the abrupt arid phases show asynchronized nature in the regional records. The more abrupt failures of the Indian Summer Monsoon during the last ~ 6000 yrs, leading to droughts in the region, seem to be at least partially governed by North Atlantic cooling events.